You have a second-degree factor and a first-degree factor in the denominator. x^2 + 1x2+1 can't be factored any further as all real numbers, so this will separate into:
A/(x - 1) + (Bx+C)/(x^2 + 1)Ax−1+Bx+Cx2+1
Cross-multiply:
= (A(x^2 + 1) + (Bx+C)(x-1))/((x-1)(x^2+1))=A(x2+1)+(Bx+C)(x−1)(x−1)(x2+1)
Multiply it out (and arrange it to look descending if you want):
= (Ax^2 + A + Bx^2 - Bx + Cx - C)/((x-1)(x^2+1))=Ax2+A+Bx2−Bx+Cx−C(x−1)(x2+1)
However you do it, you should see now that there are x^2x2, xx, and x^0x0 (constant) terms.
= (color(highlight)((A+B))x^2 + color(highlight)((-B + C))x + color(highlight)((A - C)))/((x-1)(x^2+1))=(A+B)x2+(−B+C)x+(A−C)(x−1)(x2+1)
I purposefully changed - (B - C)−(B−C) to + (-B + C)+(−B+C) to match the original numerator's adding xx. We can equate them back to the original equation's numerator terms' coefficients.
1) A + B = 1A+B=1
2) -B + C = 1−B+C=1
3) A - C = -6A−C=−6
Now, here's what I would do. The parentheses indicate which equation was used when. Single parentheses indicate newly-numbered equations.
A = 1 - BA=1−B (1)
1 - B - C = -61−B−C=−6 (1->→3)
4) B = 7 - CB=7−C
C - 7 + C = 1C−7+C=1 (4 ->→ 2)
2C = 82C=8
color(green)(C = 4)C=4
A - 4 = -6A−4=−6 (3)
color(green)(A = -2)A=−2
-2 + B = 1 -> color(green)(B = 3)−2+B=1→B=3 (1)
Plug them back in and integrate:
=> int-2/(x-1)dx + int(3x + 4)/(x^2 + 1)dx⇒∫−2x−1dx+∫3x+4x2+1dx
Notice how you can separate the second integral (some people may have trouble thinking of that):
= -2int1/(x-1)dx + int(3x)/(x^2 + 1)dx + 4int 1/(x^2 + 1)dx=−2∫1x−1dx+∫3xx2+1dx+4∫1x2+1dx
And prepare the now-second integral for u-substitution by multiplying by 3/2*2/332⋅23 since 2/3*3x = 2x23⋅3x=2x and d(x^2) = 2xdxd(x2)=2xdx:
= -2int1/(x-1)dx + 3/2int(2x)/(x^2 + 1)dx + 4int 1/(x^2 + 1)dx=−2∫1x−1dx+32∫2xx2+1dx+4∫1x2+1dx
For the first integral, it is -2ln|x-1|−2ln|x−1|. With the second one, letting u = x^2+1u=x2+1, du = 2xdxdu=2xdx (that's what we were preparing for) and thus it becomes:
3/2int1/udu32∫1udu
so it is therefore 3/2ln|x^2+1|32ln∣∣x2+1∣∣. The third is 4arctanx4arctanx since 4d/(dx)[arctanx] = 4*1/(1+x^2)4ddx[arctanx]=4⋅11+x2.
=> color(blue)(-2ln|x-1| + 3/2ln|x^2+1| + 4arctanx + C)⇒−2ln|x−1|+32ln∣∣x2+1∣∣+4arctanx+C